Antidepressive and cardioprotective effects of Kai-xin-san via the regulation of HPA axis dysfunction and lipid metabolism in a rat model of depressive-cardiac disease - Yang, Wenshan; Wang, Yuanbo; Li, Xia; Jing, Rui; Mu, Lihua; Hu, Yuan (Brain research bulletin, 2024)
Depressive-cardiac disease is a comorbid state in which both cardiovascular diseases and mental disorders are present. Patients with depression are more likely to develop cardiovascular disease, which increases the risk of cardiovascular events, such as acute coronary syndrome. Cardiovascular diseases also exacerbate the poor mood of patients with psychiatric disorders. Kai-xin-san (KXS), a classic antidepressant formula, has potential antidepressive and cardioprotective effects. In the present study, we first evaluated the antidepressive and cardioprotective effects of KXS in two post-myocardial ischemic depressed rat models: a) isoproterenol (ISO) via intraperitoneal injection combined with chronic unpredictable mild stress (CUMS)-induced myocardial ischemia and depression and b) left anterior descending coronary artery ligation (LAD) combined with chronic restraint stress (CRS)-induced myocardial ischemia and depression. We then induced exogenous corticosterone in a rat model of depressive-cardiac disease. Our study revealed that chronic administration of corticosterone could induce depression-like syndromes accompanied by cardiac insufficiency. The potential mechanism involves parallel onset of HPA axis dysfunction and an imbalance in lipid metabolism. KXS treatment successfully reversed corticosterone-induced depression-like behaviors and cardiac insufficiency. The present study highlights the pivotal role of the HPA axis and lipid metabolism in the development of comorbid depression and cardiovascular disease. Thus, KXS could be a promising therapeutic option for depressive-cardiac disease. •KXS treatment alleviates cardiac function and depressive symptoms in a rat model of postmyocardial ischemic depression.•KXS treatment alleviates cardiac function and depressive symptoms in a rat model of postmyocardial infarction depression.•The present study highlights the pivotal role of the HPA axis and lipid metabolism in the development of comorbid depression and cardiovascular disease. Thus, KXS could be a promising therapeutic option for depressive-cardiac disease.